Mitigation of learning and memory impairment caused by acute total sleep deprivation through OX1R/OX2R-mediated hippocampal neurogenesis in rats - Yixin Yu; Na Shao; Xiao Zhang; Wanyu Zhao; Baokun Zhang; Jiyou Tang; Shi Tang (Experimental Gerontology)
Sleep deprivation (SD) impairs learning and memory, which may be correlated with hippocampal neurogenesis. To observe the effects on learning and memory and hippocampal neurogenesis in the hippocampal CA1 area, we first transfected lentivirus to downregulate orexin receptor function in rats. Then, we established a rat model of 72 hourh SD. The Y-maze and Morris water maze tests were deployed to evaluate learning and memory of the rats after SD, 14 days sleep recovery and 28 days sleep recovery. Hippocampal neurogenesis was quantified using BrdU-NeuN immunofluorescence in the dentate gyrus (DG). The results showed that SD impaired learning and memory and reduced the generation of new neurons in DG. The cognition impairments were improved at 14 and 28 days after sleep recovery, but the differentiation and maturation of DG neurons were inhibited during 28 days of sleep recovery. Following the downregulated orexin receptor function after SD, the impairments of learning and memory were alleviated and DG neurogenesis were protected. We hypothesized that the downregulation in orexin receptor function could attenuate the cognition impairment by SD and exert a neuroprotective effect in hippocampus, and this process could be related to the OX1R/OX2R mediated hippocampal neurogenesis.